Telaah Perspektif Teologis dan Yuridis Islam tentang Disabilitas: dalam Buku "Islam and Disability" Karya Mohammed Ghaly - Miranda Kaira Pangestu; Sihab, Wahyu (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
The purpose of this study is to analyze Mohammed Ghaly's thoughts from a theological and legal perspective on disability and its implications for social inclusion. This research uses a qualitative approach based on literature studies with in-depth analysis of primary Islamic sources such as the Qur'an, hadith, and tafsir, kalam, and fiqh literature from various periods. Ghaly seeks to reveal the normative attitude of this religion towards persons with disabilities and its implications for social inclusion. The analysis utilizes contemporary disability studies to examine Ghaly's concepts in Islamic theology and law regarding the inherent nature and fundamental rights of persons with disabilities. However, he also emphasizes the need for new interpretations and contextualizations of this textual heritage based on the values of justice, inclusion, and empowerment. The findings of this study show that there is a stigma associated with disability due to the conflict between Islamic idealism and social reality. Nevertheless, the main principles and laws of Islam provide strong normative guidance for the dignity of persons with disabilities.